Heat transfer suppressing sheet and battery pack
By forming striped fiber bundles and inorganic particles on the heat transfer inhibiting sheet, the problem of the insulating sheet falling off under high pressure is solved, and high strength and thermal insulation performance is maintained, effectively suppressing thermal runaway and flame in the battery pack spread.
Patent Information
- Application Number
- CN202380042202.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-27
- Filing Date
- 2023-05-26
- Publication Date
- 2025-01-03
AI Technical Summary
Existing thermal insulation sheets are prone to fall off under high pressure and impact, resulting in a reduced thermal conductivity and cannot effectively suppress thermal runaway and flame spread in the battery pack.
A heat transfer inhibiting sheet with striped fiber bundles is adopted, and an island structure with organic fiber bundles and inorganic particles is formed on the surface, which is manufactured by dry molding to ensure the maintenance of high strength and thermal insulation properties.
Even under impact and pressing pressure, the heat transfer suppression sheet can maintain its shape, prevent powder from falling off, maintain excellent thermal insulation performance, and effectively suppress thermal runaway and flame spread in the battery pack.
Smart Images

Figure CN119256433A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a heat transfer suppressing sheet and a battery pack having the same. Background Art
[0002] In recent years, electric vehicles and hybrid vehicles driven by electric motors have been actively developed from the perspective of environmental protection. These electric vehicles and hybrid vehicles are equipped with a battery pack composed of a plurality of battery cells connected in series or in parallel as a power source for the driving electric motor.
[0003] In addition, lithium-ion secondary batteries are mainly used in the battery cells, which have higher capacity and higher output than lead-acid batteries, nickel-metal hydride batteries, etc. Furthermore, in the case of thermal runaway, such as a battery cell rapidly heating up and then continuously releasing heat due to internal short circuit, overcharging, etc. of the battery, the heat from the battery cell that has thermal runaway is transmitted to other adjacent battery cells, which may cause thermal runaway of other battery cells.
[0004] As a method of suppressing the propagation of heat from a battery cell that has undergone thermal runaway as described above, a method of interposing a heat insulating sheet between battery cells is generally performed.
[0005] For example, Patent Document 1 discloses a thermal insulation sheet for a battery pack, which includes first particles consisting of silica nanoparticles and second particles consisting of metal oxides, and the content of the first particles is limited. In addition, Patent Document 1 states that the thermal insulation sheet may include a binding material consisting of at least one selected from fibers, adhesives, and heat-resistant resins.
[0006] Furthermore, Patent Document 1 discloses that dry silica or wet silica can be used as the first particles, and that the thermal insulation sheet can be produced by a dry molding method or a wet papermaking method.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2021-34278 Summary of the invention
[0010] Problems to be solved by the invention
[0011] In addition, as an adhesive in the case of manufacturing a thermal insulation sheet (heat transfer suppression sheet), for example, a wet heat adhesive fiber can be cited, but the wet heat adhesive fiber needs to be in a wet state during manufacturing in order to exhibit its adhesiveness. Therefore, when using the wet heat adhesive fiber, the thermal insulation sheet needs to be manufactured by a wet papermaking method.
[0012] However, in order to further improve the thermal insulation performance, when using dry silica and silica aerogel with low thermal conductivity, there is a problem that the thermal insulation sheet cannot be manufactured by the wet papermaking method. This is because if the material containing dry silica is formed into a sheet by the wet papermaking method, the dry silica will condense due to water, and the thermal conductivity will increase. In addition, silica aerogel is usually difficult to disperse in water, so if the material containing silica aerogel is formed by the wet papermaking method, it is impossible to obtain a thermal insulation sheet with uniform material dispersion, which becomes the cause of quality reduction.
[0013] On the other hand, if inorganic particles such as dry silica and silica aerogel are used and the thermal insulation sheet is manufactured by a dry molding method, the inorganic particles may fall off (hereinafter also referred to as powder falling off) due to pressure, impact, etc. In particular, in battery packs in recent years, the capacity of battery cells has been further improved, so the expansion rate during charging and discharging has increased. Therefore, in the case where the thermal insulation sheet is arranged between battery cells in the battery pack, if the overall strength of the thermal insulation sheet is low, the thermal insulation sheet will be compressed and powder will fall off due to the expansion of the battery cells during charging and discharging of the battery cells, and the thermal insulation performance will be reduced. As a result, when the battery cells thermally run away and become high temperature, the effect of the thermal insulation sheet cannot be exerted, and thermal chain reaction may occur. From these aspects, it is required to develop the following thermal insulation sheet and its manufacturing method, which have high strength that can continuously maintain the shape, can suppress powder falling off, and can maintain excellent thermal insulation.
[0014] The thermal insulation sheet described in Patent Document 1 can maintain excellent thermal insulation even when the compressive stress increases, but further improvements are required in terms of thermal insulation, strength, and performance to suppress powder shedding.
[0015] The present invention has been completed in view of the above-mentioned problems, and its purpose is to provide a heat transfer suppression sheet and a battery pack having the heat transfer suppression sheet, wherein the heat transfer suppression sheet has strength that can maintain its shape even when impact and pressing force are applied to the heat transfer suppression sheet, thereby suppressing powder falling off and maintaining excellent insulation performance.
[0016] Means for solving problems
[0017] The above object of the present invention is achieved by the following configuration [1] of the heat transfer suppressing sheet.
[0018] [1] A heat transfer suppressing sheet comprising inorganic particles and organic fibers, characterized in that a first region having a striped fiber bundle composed of a plurality of the organic fibers and a second region where the fiber bundle is not present are formed on the surface.
[0019] Furthermore, preferred embodiments of the heat transfer suppressing sheet of the present invention relate to the following [2] to [8].
[0020] [2] The heat transfer suppressing sheet described in [1] is characterized in that the first region has the stripe-shaped fiber bundles penetrating at least three consecutive imaginary frames of 5 mm square.
[0021] [3] The heat transfer suppressing sheet described in [1] is characterized in that the first region has the striped fiber bundle having a length of 20 mm or more.
[0022] [4] The heat transfer suppression sheet according to any one of [1] to [3], comprising the second region surrounded by the first region.
[0023] [5] The heat transfer suppressing sheet according to any one of [1] to [4], wherein the striped fiber bundles are connected in a grid pattern on the surface.
[0024] [6] The heat transfer suppression sheet according to any one of [1] to [5], wherein the inorganic particles are particles composed of at least one inorganic material selected from oxide particles, carbide particles, nitride particles and inorganic hydrate particles.
[0025] [7] The heat transfer suppressing sheet according to [6], wherein the inorganic particles include at least one particle selected from dry silica particles and silica aerogel.
[0026] [8] The heat transfer suppressing sheet described in [7] is characterized in that the inorganic particles further contain particles of at least one selected from the group consisting of titanium dioxide, zircon, zirconium oxide, silicon carbide, zinc oxide, and aluminum oxide.
[0027] In addition, the above-mentioned object of the present invention is achieved by the following structure [9] of the battery pack.
[0028] [9] A battery pack comprising a plurality of battery cells and the heat transfer suppression sheet according to any one of [1] to [8], wherein the plurality of battery cells are connected in series or in parallel.
[0029] Effects of the Invention
[0030] The heat transfer suppression sheet of the present invention has a first area with striped fiber bundles and a second area without fiber bundles formed on the surface, thereby improving the strength of the heat transfer suppression sheet and alleviating the impact and pressure on the surface of the heat transfer suppression sheet, thereby suppressing powder falling off and preventing the reduction of the insulation effect due to deformation of the heat transfer suppression sheet.
[0031] According to the battery pack of the present invention, since the heat transfer suppressing sheet having high strength and heat insulation performance is included as described above, thermal runaway of battery cells in the battery pack can be suppressed and flame spread to the outside of the battery case can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a photograph in place of a drawing showing the state of the surface of the heat transfer suppression sheet according to the embodiment of the present invention.
[0033] Figure 2 It is enlarged to show Figure 1 A portion of the accompanying drawings is used in place of a photograph.
[0034] Figure 3 It is a photograph in place of a drawing showing a cross section of a heat transfer suppressing sheet according to an embodiment of the present invention.
[0035] Figure 4 This is a diagram for explaining an example of a method for determining the length of a fiber bundle, and is an enlarged view showing Figure 1 The accompanying drawings in Part A shall be used in lieu of photographs.
[0036] Figure 5 is a diagram showing a mesh-like fiber bundle, and is an enlarged diagram showing Figure 1 The accompanying drawings in Part A shall be used in lieu of photographs.
[0037] Figure 6 Schematic diagram showing a battery pack including a heat transfer suppression sheet according to an embodiment of the present invention. DETAILED DESCRIPTION
[0038] The present inventors have conducted intensive studies on a heat transfer suppressing sheet that can solve the above-mentioned problems.
[0039] As a result, it was found that by forming a first region having striped fiber bundles and a second region having no fiber bundles on the surface of a heat transfer suppressing sheet, the strength of the heat transfer suppressing sheet can be improved, thereby maintaining high thermal insulation performance.
[0040] The heat transfer suppression sheet, its manufacturing method and battery pack according to the embodiment of the present invention are described in detail below. It should be noted that the present invention is not limited to the embodiment described below, and can be implemented with any changes without departing from the scope of the present invention.
[0041] [Heat transfer suppression sheet]
[0042] Figure 1 FIG. 1 is a photograph in lieu of a drawing showing the surface of a heat transfer suppressing sheet according to an embodiment of the present invention. Figure 2 This is a photographic substitute for an enlarged view of a portion thereof. Figure 3It is a photograph in place of a drawing showing a cross section of a heat transfer suppressing sheet according to an embodiment of the present invention.
[0043] like Figure 1 to Figure 3 As shown, the heat transfer suppressing sheet 10 of the present embodiment has inorganic particles 4 and organic fibers 1. On the surface of the heat transfer suppressing sheet 10, there are formed a first region 2 having a striped fiber bundle 7 composed of a plurality of organic fibers 1, and a second region 3 where no fiber bundle 7 exists. In this specification, the fiber bundle 7 is formed by interweaving 10 or more organic fibers 1, and extends in a striped shape in a direction substantially parallel to the surface of the heat transfer suppressing sheet 10.
[0044] That is, when observing the surface of the heat transfer suppressing sheet 10, Figure 2 As shown, a plurality of organic fibers 1 are observed to be intertwined in the first region 2. On the other hand, a plurality of organic fibers 1 are observed in the second region 3, but a fiber bundle 7 formed by intertwining a plurality of organic fibers 1 is not observed.
[0045] It should be noted that, in the present embodiment, the first region 2 and the second region 3 constitute a sea-island structure, and the second region 3 corresponding to the island portion is formed so as to surround the first region 2 corresponding to the sea portion.
[0046] As a method of using the heat transfer suppression sheet 10, for example, there can be mentioned a method of sandwiching the heat transfer suppression sheet 10 between a plurality of battery cells. The specific method of using the heat transfer suppression sheet 10 is as follows.
[0047] In the present embodiment constructed as described above, the fiber bundles 7 formed by interweaving the organic fibers 1 are present in a manner extending in stripes on the surface of the heat transfer suppression sheet 10, so that the strength of the heat transfer suppression sheet 10 can be improved. In addition, since the entire surface is not covered with the fiber bundles 7, but there are the first area 2 where the fiber bundles 7 are present and the second area where the fiber bundles 7 are not present, the heat transfer suppression sheet 10 is also excellent in flexibility. In addition, since the fiber bundles 7 are present on the surface of the heat transfer suppression sheet 10, even when an impact or pressure is applied to the heat transfer suppression sheet 10, the fiber bundles 7 can absorb and mitigate the impact or pressure. Therefore, the falling off (powder falling off) of the inorganic particles 4 can be suppressed, and the reduction in the thermal insulation performance of the heat transfer suppression sheet 10 can be prevented.
[0048] It should be noted that, in this embodiment, Figure 3 As shown in the cross-sectional photograph of , the organic fibers 1 and the fiber bundles 7 formed by interweaving the organic fibers 1 exist not only on the surface of the heat transfer suppressing sheet 10 but also inside it.
[0049] This can provide even better sheet strength.
[0050] In the present embodiment, the length of the fiber bundle 7 formed so as to extend on the surface of the heat transfer suppressing sheet 10 is preferably long to a certain extent. Figure 4 An example of a method for defining the length of the fiber bundle 7 will be described.
[0051] like Figure 4 As shown in FIG. 1 , a rectangular imaginary frame 21 is arranged along the fiber bundle 7 extending in a stripe shape on the surface of the heat transfer suppressing sheet 10. In this embodiment, the size of the imaginary frame 21 is set to 5 mm square, and the imaginary frames 21 are arranged so as to be continuous with each other. At this time, if there are fiber bundles 7 penetrating at least three continuous imaginary frames 21, it can be judged that the effect of improving the strength of the heat transfer suppressing sheet 10 is sufficient.
[0052] Alternatively, the length of the fiber bundle 7 extending in a stripe shape may be simply measured. For example, a method may be used in which a string or the like is arranged on the surface of the heat transfer suppressing sheet 10 along the fiber bundle 7 and then the length of the string is measured. When the length of the continuous fiber bundle 7 is measured, if there is a fiber bundle 7 having a length of 20 mm or more, the effect of improving the strength of the heat transfer suppressing sheet 10 can be sufficiently obtained.
[0053] In addition, if Figure 5 As shown, in the heat transfer suppressing sheet 10, if the fiber bundles 7 are connected in a grid pattern on the surface thereof, the sheet strength can be further improved.
[0054] The materials constituting the heat transfer suppressing sheet of the present embodiment will be described in detail below.
[0055] <Organic Fiber>
[0056] The organic fiber 1 has the effect of imparting flexibility to the heat transfer suppressing sheet 10 and improving the strength and shape of the sheet. As the material of the organic fiber 1 in the heat transfer suppressing sheet 10, although a single-component organic fiber can also be used, it is preferable to use a core-sheath structured binder fiber. The core-sheath structured binder fiber has a core extending in the longitudinal direction of the fiber and a sheath formed in a manner covering the outer peripheral surface of the core. In addition, the core is composed of a first organic material, and the sheath is composed of a second organic material, and the melting point of the first organic material is higher than the melting point of the second organic material.
[0057] Regardless of whether a single-component organic fiber or a core-sheath structured binder fiber is used as the material of the organic fiber 1, when manufacturing the heat transfer suppressing sheet 10, a portion of the fiber surface is melted by heating, and then a fusion bond (not shown) is formed around the organic fiber 1 by cooling. Since the fusion bond fuses the inorganic particles 4 to the surface of the organic fiber 1 and fuses the organic fibers 1 to each other, excellent sheet strength can be obtained by forming the fusion bond.
[0058] When a core-sheath structured binder fiber is used as a material, in the above-mentioned heat transfer suppressing sheet 10, the core portion corresponds to the organic fiber 1. When the heat transfer suppressing sheet 10 is manufactured, if a core-sheath structured binder fiber is used, the adjacent binder fibers are fused to each other, and the fiber bundle 7 is easily formed, and the sheet strength can be further improved. In addition, if a core-sheath structured binder fiber is used, after the second organic material constituting the sheath portion is melted, it solidifies again in a state of containing the inorganic particles 4 existing around it, so that the retention force of the inorganic particles 4 can be improved.
[0059] (First organic material)
[0060] When a core-sheath structured binder fiber is used as the material of the organic fiber 1, there is no particular limitation as long as the core portion, i.e., the first organic material constituting the organic fiber 1, has a higher melting point than the sheath portion, i.e., the second organic material, present on the outer peripheral surface of the organic fiber 1. The first organic material may be at least one selected from polyethylene terephthalate, polypropylene, and nylon.
[0061] (Second organic material)
[0062] When a core-sheath structured binder fiber is used as the material of the organic fiber 1, there is no particular limitation as long as the second organic material constituting the sheath portion has a lower melting point than the first organic material constituting the organic fiber 1. The second organic material may be at least one selected from polyethylene terephthalate, polyethylene, polypropylene and nylon.
[0063] The melting point of the second organic material is preferably 90° C. or higher and 100° C. or higher. The melting point of the second organic material is preferably 150° C. or lower and more preferably 130° C. or lower.
[0064] (Organic fiber content)
[0065] In the present embodiment, if the content of the organic fiber 1 in the heat transfer suppressing sheet 10 is appropriately controlled, the effect of improving the strength of the heat transfer suppressing sheet 10 can be sufficiently obtained.
[0066] The content of the organic fiber 1 is preferably 2% by mass or more, and more preferably 4% by mass or more, relative to the total mass of the heat transfer suppression sheet 10. If the content of the organic fiber 1 is too high, the content of the inorganic particles 4 is relatively reduced. Therefore, in order to obtain the desired thermal insulation performance, the content of the organic fiber is preferably 10% by mass or less, and more preferably 8% by mass or less, relative to the total mass of the heat transfer suppression sheet 10.
[0067] (Fiber length of organic fibers)
[0068] The fiber length of the organic fibers 1 is not particularly limited, but the average fiber length of the organic fibers is preferably 10 mm or less from the viewpoint of ensuring moldability and processability.
[0069] On the other hand, from the viewpoint of improving the strength of the heat transfer suppressing sheet, the average fiber length of the organic fibers 1 is preferably 0.5 mm or more.
[0070] <Inorganic particles>
[0071] As inorganic particles, single inorganic particles can be used, and more than two kinds of inorganic particles can be used in combination. As the kind of inorganic particles, from the aspect of heat transfer inhibition effect, preferably use the particles consisting of at least one inorganic material selected from oxide particles, carbide particles, nitride particles and inorganic hydrate particles, more preferably use oxide particles. In addition, shape is not particularly limited yet, preferably comprises at least one selected from nanoparticles, hollow particles and porous particles, specifically, inorganic hollow balls such as silicon dioxide nanoparticles, metal oxide particles, microporous particles, hollow silicon dioxide particles, particles consisting of thermally expansive inorganic materials, particles consisting of water-containing porous bodies, etc. can also be used.
[0072] If the average secondary particle size of the inorganic particles is 0.01 μm or more, it is easy to obtain and the increase in manufacturing costs can be suppressed. In addition, if the average secondary particle size is 200 μm or less, the desired insulation effect can be obtained. Therefore, the average secondary particle size of the inorganic particles is preferably 0.01 μm or more and 200 μm or less, and more preferably 0.05 μm or more and 100 μm or less.
[0073] It should be noted that, if two or more inorganic particles with different heat transfer inhibition effects are used together, the exothermic body can be cooled in multiple stages, and endothermic effect can be shown in a wider temperature range. Specifically, it is preferred that large diameter particles and small diameter particles are mixed for use. For example, when using nanoparticles as one inorganic particle, as the other inorganic particle, it is preferred to include inorganic particles consisting of metal oxides. Hereinafter, the inorganic particles of small diameter are used as the first inorganic particles, and the inorganic particles of large diameter are used as the second inorganic particles, and the inorganic particles are further described in detail.
[0074] <First Inorganic Particles>
[0075] (Oxide particles)
[0076] The refractive index of oxide particles is high, and the effect of diffuse reflection of light is strong. Therefore, when oxide particles are used as the first inorganic particles, radiative heat transfer can be suppressed, especially in high temperature areas such as abnormal heat release. As oxide particles, particles selected from at least one of silica, titania, zirconium oxide, zircon, barium titanate, zinc oxide and aluminum oxide can be used. That is, among the above-mentioned oxide particles that can be used as inorganic particles, only one type can be used, or two or more types of oxide particles can be used. In particular, silica is a component with high thermal insulation, and titania is a component with a higher refractive index than other metal oxides. It has a high effect of diffuse reflection of light and shielding radiant heat in high temperature areas above 500°C. Therefore, it is most preferred to use silica and titania as oxide particles.
[0077] (Average primary particle size of oxide particles: 0.001 μm or more and 50 μm or less)
[0078] The particle size of the oxide particles may affect the effect of reflecting radiant heat, so if the average primary particle size is limited to a predetermined range, higher thermal insulation properties can be obtained.
[0079] That is, if the average primary particle size of the oxide particles is greater than 0.001 μm, it is sufficiently larger than the wavelength of light that contributes to heating, so that the light is efficiently diffusely reflected. Therefore, in the high temperature region above 500°C, the radiation heat transfer in the heat transfer suppression sheet is suppressed, and the thermal insulation can be further improved.
[0080] On the other hand, if the average primary particle size of the oxide particles is less than 50 μm, the number of contact points between the particles will not increase even if they are compressed, making it difficult to form a path for conductive heat transfer. Therefore, the effect on thermal insulation can be particularly reduced in the normal temperature range where conductive heat transfer is dominant.
[0081] In the present invention, the average primary particle size can be determined by observing the particles with a microscope, comparing with a standard scale, and taking the average value of any 10 particles.
[0082] (Nanoparticles)
[0083] In the present invention, nanoparticles refer to nano-scale particles with a spherical or nearly spherical average primary particle size of less than 1 μm. Since nanoparticles are low-density, conductive heat transfer can be suppressed. If nanoparticles are used as the first inorganic particles, the gaps are further finely dispersed, so excellent thermal insulation that suppresses convective heat transfer can be obtained. Therefore, when using the battery in a normal temperature region, heat conduction between adjacent nanoparticles can be suppressed. From this aspect, nanoparticles are preferably used.
[0084] In addition, if nanoparticles with a small average primary particle size are used as oxide particles, even if the heat transfer suppression sheet is compressed due to expansion associated with thermal runaway of the battery cell and the internal density increases, the increase in conductive heat transfer of the heat transfer suppression sheet can be suppressed. It is believed that this is because nanoparticles are easily filled with fine gaps between particles due to the repulsive force caused by static electricity, and the packing density is low, so the particles are filled in a manner with buffering properties.
[0085] It should be noted that, in the present invention, when nanoparticles are used as the first inorganic particles, the material is not particularly limited as long as it meets the above-mentioned definition of nanoparticles. For example, silicon dioxide nanoparticles are a material with high thermal insulation properties, and the contact points between the particles are small. Therefore, compared with the case of using silicon dioxide particles with large particle sizes, the heat conducted by the silicon dioxide nanoparticles is reduced. In addition, the bulk density of the silicon dioxide nanoparticles usually obtained is 0.1 (g / cm 3 ), so for example, even if the battery cells arranged on both sides of the heat transfer suppression sheet undergo thermal expansion and a large compressive stress is applied to the heat transfer suppression sheet, the size (area) and number of the contact points between the silica nanoparticles will not increase significantly, and the thermal insulation can be maintained. Therefore, as nanoparticles, silica nanoparticles are preferably used. Examples of silica nanoparticles include wet silica, dry silica, and aerogel, and silica nanoparticles that are particularly suitable for this embodiment are described below.
[0086] Generally, in wet silica, particles are aggregated together, whereas in dry silica, particles can be dispersed. In the temperature range below 300°C, heat transfer is dominated by conduction, so dry silica, whose particles can be dispersed, can obtain excellent thermal insulation performance compared to wet silica.
[0087] It should be noted that the heat transfer suppressing sheet of the present embodiment is preferably produced by a method of processing a mixture containing materials into a sheet by a dry method. Therefore, dry silica, silica aerogel, etc. having low thermal conductivity are preferably used as inorganic particles.
[0088] (Average primary particle size of nanoparticles: 1 nm or more and 100 nm or less)
[0089] When the average primary particle size of the nanoparticles is limited to a predetermined range, higher thermal insulation properties can be obtained.
[0090] That is, if the average primary particle size of the nanoparticles is set to be between 1 nm and 100 nm, the convection heat transfer and conduction heat transfer in the heat transfer suppression sheet can be suppressed, especially in the temperature range below 500° C., and the thermal insulation can be further improved. In addition, even when compressive stress is applied, the gaps remaining between the nanoparticles and the contact points between the multiple particles can suppress the conduction heat transfer, and the thermal insulation of the heat transfer suppression sheet can be maintained.
[0091] It should be noted that the average primary particle size of the nanoparticles is more preferably 2 nm or more, and further preferably 3 nm or more. On the other hand, the average primary particle size of the nanoparticles is more preferably 50 nm or less, and further preferably 10 nm or less.
[0092] (Inorganic hydrate particles)
[0093] When the inorganic hydrate particles are exposed to heat from the exothermic body and reach a temperature above the thermal decomposition starting temperature, they will thermally decompose, releasing their own crystal water and lowering the temperature of the exothermic body and its surroundings, thus exhibiting a so-called "endothermic effect". In addition, after releasing the crystal water, they become porous and exhibit a heat-insulating effect through countless air pores.
[0094] Specific examples of inorganic hydrates include aluminum hydroxide (Al(OH) 3 )、Magnesium hydroxide (Mg(OH) 2 ), calcium hydroxide (Ca(OH) 2 )、Zn(OH) 2 ), ferric hydroxide (Fe(OH) 2 ), manganese hydroxide (Mn(OH) 2 )、Zr(OH) 2 ), gallium hydroxide (Ga(OH) 3 )wait.
[0095] For example, aluminum hydroxide has about 35% of crystal water, and as shown in the following formula, it undergoes thermal decomposition to release crystal water, exhibiting an endothermic effect. And, after releasing crystal water, it becomes aluminum oxide (Al 2 O 3 ), and functions as a thermal insulator.
[0096] 2Al(OH) 3 →Al 2 O 3 +3H 2 O
[0097] It should be noted that, as described below, the heat transfer suppression sheet 10 of the present embodiment is suitable for being interposed between battery cells, for example, but in a battery cell that has thermal runaway, the temperature rises sharply to more than 200° C., and the temperature continues to rise to around 700° C. Therefore, the inorganic particles are preferably composed of an inorganic hydrate having a thermal decomposition starting temperature of 200° C. or more.
[0098] Regarding the thermal decomposition starting temperatures of the inorganic hydrates listed above, aluminum hydroxide is about 200°C, magnesium hydroxide is about 330°C, calcium hydroxide is about 580°C, zinc hydroxide is about 200°C, iron hydroxide is about 350°C, manganese hydroxide is about 300°C, zirconium hydroxide is about 300°C, and gallium hydroxide is about 300°C. They all roughly overlap with the temperature range of the rapid temperature rise of the battery cell when thermal runaway occurs, and can effectively suppress the temperature rise. Therefore, they can be said to be preferred inorganic hydrates.
[0099] (Average secondary particle size of inorganic hydrate particles: 0.01 μm or more and 200 μm or less)
[0100] In addition, when inorganic hydrate particles are used as the first inorganic particles, if the average particle size is too large, it takes a certain amount of time for the first inorganic particles (inorganic hydrate) located near the center of the heat transfer suppressing sheet 10 to reach their thermal decomposition temperature, so there is a case where the first inorganic particles near the center of the sheet cannot be completely thermally decomposed. Therefore, the average secondary particle size of the inorganic hydrate particles is preferably 0.01 μm to 200 μm, and more preferably 0.05 μm to 100 μm.
[0101] (Particles composed of heat-expandable inorganic material)
[0102] Examples of the thermally expandable inorganic material include vermiculite, bentonite, mica, and perlite.
[0103] (Particles composed of a porous body containing water)
[0104] Specific examples of the hydrous porous body include zeolite, kaolinite, montmorillonite, acid clay, diatomaceous earth, wet silica, dry silica, aerogel, mica, vermiculite and the like.
[0105] (Inorganic hollow sphere)
[0106] The heat transfer suppressing sheet 10 of the present embodiment may contain inorganic hollow spheres as the first inorganic particles.
[0107] When the inorganic hollow spheres are included, convection heat transfer or conductive heat transfer of heat in the heat transfer suppression sheet can be suppressed in a temperature range lower than 500° C., and the thermal insulation property of the heat transfer suppression sheet can be further improved.
[0108] As the inorganic hollow sphere, at least one selected from the group consisting of volcanic ash hollow spheres, silica hollow spheres, fly ash hollow spheres, barite hollow spheres, and glass hollow spheres can be used.
[0109] (Content of inorganic hollow spheres: 60% by mass or less relative to the total mass of the thermal insulation material)
[0110] The content of the inorganic hollow spheres is preferably 60% by mass or less based on the total mass of the thermal insulation material.
[0111] (Average particle size of inorganic hollow spheres: 1 μm or more and 100 μm or less)
[0112] The average particle size of the inorganic hollow spheres is preferably 1 μm or more and 100 μm or less.
[0113] <Second Inorganic Particles>
[0114] When the heat transfer inhibition sheet contains two kinds of inorganic particles, the second inorganic particle is not particularly limited as long as the material, particle size, etc. are different from the first inorganic particle. As the second inorganic particle, inorganic hollow spheres such as oxide particles, carbide particles, nitride particles, inorganic hydrate particles, silicon dioxide nanoparticles, metal oxide particles, microporous particles, hollow silicon dioxide particles, particles made of thermally expandable inorganic materials, particles made of water-containing porous bodies, etc. can be used, and their details are as described above.
[0115] It should be noted that the conduction heat transfer of nanoparticles is extremely small, and even when compressive stress is applied to the heat transfer suppression sheet, excellent thermal insulation can be maintained. In addition, metal oxide particles such as titanium dioxide have a high effect of shielding radiant heat. Furthermore, if large-diameter inorganic particles and small-diameter inorganic particles are used, the small-diameter inorganic particles will enter the gaps between the large-diameter inorganic particles, thereby forming a denser structure, which can improve the heat transfer suppression effect. Therefore, when using, for example, nanoparticles as the above-mentioned first inorganic particles, it is preferred that the heat transfer suppression sheet further contains particles composed of metal oxides having a larger diameter than the first inorganic particles as the second inorganic particles.
[0116] Examples of the metal oxide include silicon oxide, titanium oxide, aluminum oxide, barium titanate, zinc oxide, zircon, zirconium oxide, etc. Titanium oxide (titanium dioxide) is a component with a higher refractive index than other metal oxides, and has a high effect of diffusely reflecting light and shielding radiant heat in a high temperature region of 500° C. or higher, so titanium dioxide is most preferably used.
[0117] When at least one particle selected from dry silica particles and silica aerogel is used as the first inorganic particle and at least one particle selected from titanium dioxide, zircon, zirconium oxide, silicon carbide, zinc oxide, and aluminum oxide is used as the second inorganic particle, in order to obtain excellent thermal insulation performance in a temperature range of 300° C. or less, the first inorganic particle is preferably 50% by mass or more, more preferably 60% by mass or more, and further preferably 70% by mass or more relative to the total mass of the inorganic particles. In addition, the first inorganic particle is preferably 95% by mass or less, more preferably 90% by mass or less, and further preferably 80% by mass or less relative to the total mass of the inorganic particles.
[0118] On the other hand, in order to obtain excellent thermal insulation performance in a temperature range exceeding 300° C., the second inorganic particles are preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 20% by mass or more relative to the total mass of the inorganic particles. In addition, the second inorganic particles are preferably 50% by mass or less, more preferably 40% by mass or less, and further preferably 30% by mass or less relative to the total mass of the inorganic particles.
[0119] (Average primary particle size of second inorganic particles)
[0120] When the heat transfer suppressing sheet contains second inorganic particles composed of metal oxide, if the average primary particle size of the second inorganic particles is 1 μm to 50 μm, radiant heat transfer can be effectively suppressed in a high temperature region of 500° C. or higher. The average primary particle size of the second inorganic particles is more preferably 5 μm to 30 μm, and most preferably 10 μm or less.
[0121] (Content of Inorganic Particles)
[0122] In the present embodiment, if the total content of the inorganic particles 4 in the heat transfer suppression sheet 10 is appropriately controlled, the heat insulating property of the heat transfer suppression sheet 10 can be sufficiently ensured.
[0123] The total content of the inorganic particles 4 is preferably 60% by mass or more, and more preferably 70% by mass or more, relative to the total mass of the heat transfer suppression sheet 10. In addition, if the total content of the inorganic particles 4 is too large, the content of the organic fibers 1 is relatively reduced. Therefore, in order to fully obtain the effect of improving the sheet strength based on the organic fibers 1, the total content of the inorganic particles 4 is preferably 95% by mass or less, and more preferably 90% by mass or less, relative to the total mass of the heat transfer suppression sheet 10.
[0124] The content of the inorganic particles 4 in the heat transfer suppressing sheet 10 can be calculated by, for example, heating the heat transfer suppressing sheet 10 at 800° C. to decompose the organic component and then measuring the mass of the remaining portion.
[0125] The heat transfer suppressing sheet 10 of this embodiment may include organic fibers and inorganic fibers made of an organic material different from the first organic material in addition to the organic fibers 1 and inorganic particles 4. When the heat transfer suppressing sheet 10 includes inorganic fibers, inorganic fibers preferably included in this embodiment will be described below.
[0126] <Inorganic Fiber>
[0127] As the inorganic fiber, a single inorganic fiber can be used, or two or more inorganic fibers can be used in combination. As the inorganic fiber, for example, silica fiber, alumina fiber, aluminum silicate fiber, zirconium oxide fiber, carbon fiber, soluble fiber, refractory ceramic fiber, aerogel composite material, magnesium silicate fiber, alkaline earth silicate fiber, potassium titanate fiber, silicon carbide fiber, potassium titanate whisker fiber and other ceramic fibers, glass fiber, glass wool, slag wool and other glass fibers, rock wool, basalt fiber, mullite fiber, as mineral fibers other than the above natural mineral fibers such as wollastonite, etc. can be cited.
[0128] These inorganic fibers are preferred from the viewpoint of heat resistance, strength, availability, etc. Among the inorganic fibers, silica-alumina fibers, alumina fibers, silica fibers, rock wool, alkaline earth silicate fibers, and glass fibers are particularly preferred from the viewpoint of handleability.
[0129] The cross-sectional shape of the inorganic fiber is not particularly limited, and examples thereof include circular cross-section, flat cross-section, hollow cross-section, polygonal cross-section, core cross-section, etc. Among them, fibers with a hollow cross-section, flat cross-section or polygonal cross-section are preferably used because they have slightly higher thermal insulation properties.
[0130] The preferred lower limit of the average fiber length of the inorganic fibers is 0.1 mm, and the more preferred lower limit is 0.5 mm. On the other hand, the preferred upper limit of the average fiber length of the inorganic fibers is 50 mm, and the more preferred upper limit is 10 mm. If the average fiber length of the inorganic fibers is less than 0.1 mm, it is not easy for the inorganic fibers to be entangled with each other, and the mechanical strength of the heat transfer suppression sheet 10 may be reduced. On the other hand, if it exceeds 50 mm, although a reinforcement effect can be obtained, the inorganic fibers cannot be tightly entangled with each other, or only a single inorganic fiber is curled, which easily produces continuous gaps, thereby possibly causing a reduction in thermal insulation.
[0131] The preferred lower limit of the average fiber diameter of the inorganic fibers is 1 μm, the more preferred lower limit is 2 μm, and the further preferred lower limit is 3 μm. On the other hand, the preferred upper limit of the average fiber diameter of the inorganic fibers is 15 μm, and the more preferred upper limit is 10 μm. If the average fiber diameter of the inorganic fibers is less than 1 μm, the mechanical strength of the inorganic fibers themselves may be reduced. In addition, from the perspective of the impact on human health, the average fiber diameter of the inorganic fibers is preferably greater than 3 μm. On the other hand, if the average fiber diameter of the inorganic fibers is greater than 15 μm, the solid heat transfer using the inorganic fibers as a medium increases, which may lead to a decrease in thermal insulation. In addition, the formability and strength of the heat transfer suppression sheet may deteriorate.
[0132] (Inorganic fiber content)
[0133] In the present embodiment, when the heat transfer suppression sheet 10 includes inorganic fibers, the content of the inorganic fibers is preferably 3 mass % or more and 15 mass % or less relative to the total mass of the heat transfer suppression sheet 10 .
[0134] In addition, the content of the inorganic fiber is more preferably 5% by mass or more and 10% by mass or less relative to the total mass of the heat transfer suppression sheet 10. By setting such a content, the shape retention, pressure resistance, wind pressure resistance, and inorganic particle retention capacity based on the inorganic fiber can be well balanced. In addition, by appropriately controlling the content of the inorganic fiber, the organic fiber 1 and the inorganic fiber are entangled with each other to form a three-dimensional network, so that the effect of retaining the inorganic particles 4 and other mixed materials described later can be further improved.
[0135] <Other mixed materials>
[0136] It should be noted that the heat transfer suppressing sheet of this embodiment may further contain a binder, a colorant, etc. as needed. These are useful for the purpose of reinforcing the heat transfer suppressing sheet, improving the moldability, etc., and the total amount is preferably 10% by mass or less relative to the total mass of the heat transfer suppressing sheet.
[0137] [Method for producing heat transfer suppressing sheet]
[0138] Hereinafter, an example of a method for manufacturing the heat transfer suppression sheet 10 according to the present embodiment will be described.
[0139] For example, binder fibers (not shown) having a core-sheath structure and inorganic particles 4 are put into a mixer such as a V-type mixer at a predetermined ratio to prepare a mixture.
[0140] As described above, the binder fiber preferably has a core-sheath structure in which the core is made of a first organic material and the sheath is made of a second organic material. In this case, the melting point of the first organic material is higher than that of the second organic material.
[0141] After that, the obtained mixture is put into a predetermined mold, pressurized by a press machine or the like, and the obtained molded body is heated, thereby melting the sheath of the binder fiber. The heated molded body is then cooled, thereby solidifying the molten sheath on the surface of the molded body, and the core (organic fiber 1) is welded to each other, thereby forming a fiber bundle 7 on the surface of the heat transfer suppressing sheet 10. In addition, inside the molded body, the second organic material constituting the molten sheath and the inorganic particles 4 present around the binder fiber are welded to the core, and are also welded to each other in the area where the binder fibers are in contact with each other. In this way, the heat transfer suppressing sheet 10 of this embodiment can be obtained.
[0142] In this embodiment, the heat transfer suppression sheet 10 is preferably manufactured by a dry method. When the dry method is used, inorganic particles 4 suitable for the dry method are used, and a solvent such as water required for molding by a wet method is not added to the above-mentioned mixture. However, when manufacturing the heat transfer suppression sheet 10, in order to prevent the inorganic particles 4 and other powders from flying and making the handling of the raw materials difficult, a small amount of water or other solvents may be added within the range considered as a dry method. For example, by adding a small amount of solvent such as water to the mixture, the scattering of inorganic particles during manufacturing can be suppressed.
[0143] According to the manufacturing method of the present embodiment, since a fiber bundle 7 composed of organic fibers 1 is formed on the surface, a heat transfer suppression sheet 10 having excellent strength can be manufactured. In addition, since the melting point of the first organic material constituting the core is higher than the melting point of the second organic material constituting the sheath, when the mixture is heated, the core can be left and the sheath can be melted. Moreover, after cooling, the outer peripheral surface of the core is coated with the second organic material containing inorganic particles 4, so that the inorganic particles 4 can be retained. The organic fibers 1 fused with the inorganic particles 4 have an apparently thick fiber diameter, so the strength is higher than the strength of the organic fibers 1 alone. In addition, in the mixture, the adhesive fibers exist in irregular directions, so in the area where the adhesive fibers are in contact with each other, the organic fibers 1 are fused to each other to form a three-dimensional skeleton. As a result, the overall shape of the heat transfer suppression sheet can be maintained with higher strength.
[0144] It should be noted that even when an organic fiber without a core-sheath structure is used as a binder fiber, a fiber bundle 7 extending in a stripe shape can be formed on the surface. However, when manufacturing a heat transfer suppressing sheet, heating is usually performed from one side or both sides orthogonal to the thickness direction. Since a material with high thermal insulation performance is used, it is difficult to raise the temperature to the same level on the surface side and inside of the sheet. On the surface side of the sheet, the temperature is controlled so that multiple organic fibers do not melt excessively, and inside the sheet, only the surface of the organic fiber is melted, the inorganic particles are covered on the surface, or the organic fibers are fused to each other. In order to manufacture a heat transfer suppressing sheet 10 with further improved sheet strength, strict temperature management is required.
[0145] On the other hand, if a binder fiber having a core-sheath structure is used in which the melting point of the first organic material constituting the core is higher than the melting point of the second organic material constituting the sheath, the temperature for melting the sheath while leaving the core can be set very easily. As a result, the obtained heat transfer suppressing sheet has an ideal structure in which the organic fibers 1 are fused to each other on both the surface side and the center side to form a skeleton that improves the strength of the sheet, and the inorganic particles 4 are fused to the surface of the organic fibers 1. Therefore, as a material for the heat transfer suppressing sheet 10, it is preferable to use a binder fiber having the core-sheath structure described above.
[0146] It should be noted that as the raw material of the heat transfer suppression sheet, the mixture may also contain adhesives such as hot melt powder, which will be described in detail below. By properly adjusting the type and content of the adhesive contained in the mixture, the retention of the inorganic particles 4 can be improved and the powder can be further suppressed from falling off.
[0147] As a result, the heat transfer suppression sheet 10 manufactured by the manufacturing method of this embodiment has higher strength, can maintain its shape even when a pressing force or impact is applied to the heat transfer suppression sheet, can suppress powder falling, and can maintain excellent thermal insulation performance.
[0148] It should be noted that, in order to further suppress the falling of powder, the surface of the heat transfer suppression sheet 10 may be coated with a film or the like. Examples of the polymer film include films made of polyimide, polycarbonate, PET, polyphenylene sulfide, polyetherimide, cross-linked polyethylene, flame retardant chloroprene rubber, polyvinylidene fluoride, rigid vinyl chloride, polybutylene terephthalate, PTFE, PFA, FEP, ETFE, rigid PCV, flame retardant PET, polystyrene, polyethersulfone, polyamide-imide, polyacrylonitrile, polyethylene, polypropylene, polyamide, etc. It should be noted that there is no particular limitation on the method of coating the surface of the heat transfer suppression sheet 10 with a film, and examples include a method of pasting with an adhesive or the like, a method of wrapping the heat transfer suppression sheet 10 with a film, and a method of housing the heat transfer suppression sheet 10 in a bag-like film.
[0149] Next, the binder fibers and heating conditions preferably used in the method for producing the heat transfer suppressing sheet of the present embodiment will be described.
[0150] <Binder Fiber>
[0151] In this embodiment, when a core-sheath structured binder fiber is used, there is no particular limitation as long as the melting point of the first organic material constituting the core is higher than the melting point of the second organic material constituting the sheath. As the first organic material constituting the core, at least one selected from polyethylene terephthalate, polypropylene and nylon can be selected. In addition, as the second organic material constituting the sheath, at least one selected from polyethylene terephthalate, polyethylene, polypropylene and nylon can be selected.
[0152] If the melting point of the first organic material constituting the core is sufficiently higher than the melting point of the second organic material constituting the sheath, the setting margin of the heating temperature in the heating process can be expanded, and the temperature setting for obtaining the desired structure can be further easily performed. For example, the melting point of the first organic material is preferably higher than the melting point of the second organic material by 60°C or more, more preferably higher by 70°C or more, and further preferably higher by 80°C or more.
[0153] It should be noted that adhesive fibers having a core-sheath structure as described above are generally sold on the market, and the materials constituting the core and the sheath may be the same or different. Examples of adhesive fibers having the same material as the core and the sheath but different melting points include: fibers having a core and a sheath made of polyethylene terephthalate; fibers having a core and a sheath made of polypropylene; fibers having a core and a sheath made of nylon; and the like. Examples of adhesive fibers having a core and a sheath made of different materials include fibers having a core made of polyethylene terephthalate and a sheath made of polyethylene; fibers having a core made of polypropylene and a sheath made of polyethylene; and the like.
[0154] In this embodiment, the melting point of the second organic material constituting the sheath of the binder fiber means the melting temperature at which the second organic material starts to melt and deform, and softening accompanied by shape change is also considered as a type of melting and deformation. The melting point of the sheath of the binder fiber can be measured, for example, by the following method.
[0155] The binder fiber to be measured is arranged in such a manner as to contact the glass fiber having a higher melting point, and is heated from room temperature to, for example, 200°C at a heating rate of 5°C / min, and then cooled to room temperature. At this time, if the surface of the binder fiber undergoes melting deformation and fusion occurs at the portion in contact with the glass fiber, or if the cross-sectional shape of the binder fiber changes, it can be determined that the melting point of the second organic material constituting the sheath portion is 200°C or less. In this embodiment, the heating temperature is varied, and the fusion state of the binder fiber and the glass fiber after cooling or the cross-sectional shape of the binder fiber is observed by the above method, thereby determining the melting point of the second organic material constituting the sheath portion.
[0156] (Content of Binder Fiber)
[0157] In the present embodiment, when a core-sheath structured binder fiber is used as a material, if the content of the binder fiber in the mixture is appropriately controlled, fiber bundles 7 of appropriate length can be formed on the surface of the resulting heat transfer suppressing sheet 10, and excellent sheet strength can be obtained.
[0158] The content of the binder fiber is preferably 5% by mass or more, more preferably 10% by mass or more, relative to the total mass of the mixture. In addition, if the content of the binder fiber is too much, the content of the inorganic particles 4 is relatively reduced. Therefore, in order to obtain the desired thermal insulation performance, the content of the binder fiber is preferably 25% by mass or less, more preferably 20% by mass or less, relative to the total mass of the mixture.
[0159] <Hot-melt powder>
[0160] In this embodiment, in addition to the above-mentioned binder fibers and inorganic particles 4, hot-melt powder may also be contained in the mixture. The hot-melt powder is, for example, a powder containing a third organic material different from the above-mentioned first organic material and second organic material and having the property of melting by heating. By making the mixture contain hot-melt powder and heating it, the hot-melt powder melts, and when it is cooled, it solidifies in a state of containing the surrounding inorganic particles 4. Therefore, it is possible to further suppress the inorganic particles 4 from falling off from the heat transfer suppression sheet 10.
[0161] As the hot-melt powder, there are hot-melt powders having various melting points. Considering the melting points of the core and sheath of the binder fiber used, a hot-melt powder having an appropriate melting point can be selected. Specifically, if the third organic material as a component constituting the hot-melt powder has a lower melting point than the first organic material constituting the organic fiber, it is possible to set a heating temperature for melting the sheath and the hot-melt powder while leaving the core. For example, if the melting point of the hot-melt powder is lower than the melting point of the sheath, the heating temperature during manufacturing can be set between the melting point of the core and the melting point of the sheath, so that the heating temperature can be set more easily.
[0162] On the other hand, the type of hot-melt powder used can also be selected in such a way that the melting point of the hot-melt powder is between the melting point of the core and the melting point of the sheath. If a hot-melt powder with such a melting point is used, when the sheath and the hot-melt powder are both melted and then cooled to solidify, the organic fiber (core) 1 and the surrounding melted sheath, as well as the hot-melt powder present in the gaps between the inorganic particles 4, solidify first. As a result, the position of the organic fiber 1 can be fixed, and then the melted sheath is welded to the organic fiber, thereby easily forming a three-dimensional skeleton. Therefore, the strength of the entire sheet can be further improved.
[0163] If the melting point of the third organic material constituting the hot-melt powder is sufficiently lower than the melting point of the first organic material constituting the core, the setting margin of the heating temperature in the heating process can be expanded, and the temperature for obtaining the desired structure can be set more easily. For example, the melting point of the first organic material is preferably higher than the melting point of the third organic material by 60°C or more, more preferably higher by 70°C or more, and further preferably higher by 80°C or more.
[0164] It should be noted that the melting point of the hot-melt powder (third organic material) is preferably 80° C. or higher, more preferably 90° C. or higher. In addition, the melting point of the hot-melt powder (third organic material) is preferably 180° C. or lower, more preferably 150° C. or lower. Components constituting the hot-melt powder include polyethylene, polyester, polyamide, ethylene vinyl acetate, and the like.
[0165] (Content of hot melt powder)
[0166] When hot-melt powder is contained in the mixture to suppress the falling of inorganic particles, even a small amount thereof can achieve the effect of suppressing the falling of powder. Therefore, the content of hot-melt powder is preferably 0.5% by mass or more, more preferably 1% by mass or more relative to the total mass of the mixture.
[0167] On the other hand, if the content of the hot-melt powder is increased, the content of the inorganic particles 4 etc. will relatively decrease. Therefore, in order to obtain the desired thermal insulation performance, the content of the hot-melt powder is preferably 5% by mass or less, more preferably 4% by mass or less relative to the total mass of the mixture.
[0168] <Heating conditions>
[0169] As the process of processing the above-mentioned mixture into a sheet, there can be cited a process of pressurizing the mixture and a process of heating the mixture. When a core-sheath structured binder fiber is used as the material of the heat transfer suppressing sheet 10, it is preferred that the heating temperature in the heating process is a temperature higher than the melting point of the second organic material constituting the sheath and lower than the melting point of the first organic material constituting the core. By setting such a heating temperature, as described above, the strength of the sheet can be ensured by the core on either side of the surface side or the center side of the sheet, and the inorganic particles 4 can be retained by the fused sheath.
[0170] Specifically, the heating temperature in the heating step is preferably set to be 10° C. or higher than the melting point of the second organic material constituting the sheath, and more preferably 20° C. or higher. On the other hand, the heating temperature is preferably set to be 10° C. or lower than the melting point of the first organic material constituting the core, and more preferably 20° C. or lower.
[0171] The heating time is not particularly limited, but is preferably set to a heating time that allows the sheath portion to be sufficiently melted, and can be set, for example, to a time of 3 minutes or more and 15 minutes or less.
[0172] In the case where the heat transfer suppressing sheet includes a hot-melt powder as the material, the heating temperature in the heating step is preferably set to be 10°C or higher than the higher melting point of the second organic material constituting the sheath and the melting point of the third organic material constituting the hot-melt powder, and more preferably set to be 20°C or higher. On the other hand, the heating temperature is preferably set to be 10°C or lower than the melting point of the first organic material constituting the core, and more preferably set to be 20°C or lower. By setting the heating temperature to such a temperature, a strong skeleton can be formed, the strength of the sheet can be further improved, and the inorganic particles 4 can be prevented from falling off.
[0173] <Thickness of Heat Transfer Suppression Sheet>
[0174] The thickness of the heat transfer suppression sheet of this embodiment is not particularly limited, and is preferably 0.05 mm or more and 10 mm or less. If the thickness is 0.05 mm or more, sufficient compressive strength can be obtained. On the other hand, if the thickness is 10 mm or less, good thermal insulation of the heat transfer suppression sheet can be obtained.
[0175] [Battery Pack]
[0176] Figure 6 Schematic diagram showing a battery pack having a heat transfer suppression sheet according to an embodiment of the present invention. Figure 6 As shown, the battery pack 100 includes a plurality of battery cells 20a, 20b, and 20c and the heat transfer suppressing sheet 10 of the present embodiment, and the plurality of battery cells 20a, 20b, and 20c are connected in series or in parallel.
[0177] Specifically, the heat transfer suppression sheet 10 is interposed between the battery cell 20a and the battery cell 20b, and between the battery cell 20b and the battery cell 20c. The battery pack 100 is formed by housing the battery case 30 with the plurality of battery cells 20a, 20b, and 20c connected in series or in parallel (the connection state is not shown). It should be noted that the battery cells 20a, 20b, and 20c are suitably used in, for example, lithium-ion secondary batteries, but are not particularly limited thereto and may also be applied to other secondary batteries.
[0178] In addition, the heat transfer suppressing sheet 10 is as described above.
[0179] In the battery pack 100 configured as above, even if a battery cell 20a reaches a high temperature, the heat transfer suppressing sheet 10 having a heat transfer suppressing effect is present between the battery cell 20a and the battery cell 20b, thereby suppressing the heat transfer to the battery cell 20b.
[0180] In addition, the heat transfer suppression sheet 10 of this embodiment has high strength, can absorb impact, and has the effect of resisting pressing force, so it can also suppress the thermal expansion of the battery cells 20a, 20b, and 20c during charging and discharging. Therefore, the distance between the battery cells can be ensured, and excellent insulation performance can be maintained, so that thermal runaway of the battery cells can be prevented. In addition, since it has the effect of suppressing the shedding of powder, it can be easily handled.
[0181] It should be noted that the battery pack 100 of this embodiment is not limited to Figure 6 For example, the heat transfer suppression sheet 10 is not only disposed between the battery cells 20a and 20b and between the battery cells 20b and 20c, but also disposed between the battery cells 20a, 20b, 20c and the battery case 30, or attached to the inner surface of the battery case 30.
[0182] In the battery pack 100 configured in this manner, when a battery cell catches fire, it is possible to suppress the flame from spreading to the outside of the battery case 30 .
[0183] For example, the battery pack 100 of the present embodiment may be used in an electric vehicle (EV) or the like and may be placed under the floor of a passenger. In this case, even if a battery cell catches fire, the safety of the passenger can be ensured.
[0184] Furthermore, the heat transfer suppression sheet 10 can be interposed not only between the battery cells but also between the battery cells 20a, 20b, 20c and the battery case 30, so that there is no need to re-produce fireproofing materials, etc., and a low-cost and safe battery pack 100 can be easily constructed.
[0185] In the battery pack of this embodiment, the heat transfer suppression sheet 10 disposed between the battery cells 20a, 20b, 20c and the battery case 30 may be in contact with the battery cells or may have a gap therebetween. However, if there is a gap between the heat transfer suppression sheet 10 and the battery cells 20a, 20b, 20c, even if the temperature of any of the plurality of battery cells rises and the volume expands, deformation of the battery cell can be allowed.
[0186] It should be noted that the heat transfer suppression sheet 10 of this embodiment can be made into various shapes by its manufacturing method. Therefore, it can cope with any shape without being affected by the shape of the battery cells 20a, 20b, 20c and the battery case 30. Specifically, in addition to square batteries, it can also be applied to cylindrical batteries, flat batteries, etc.
[0187] Various embodiments have been described above, but the present invention is certainly not limited to such examples. As long as it is clear to those skilled in the art, various variations or modifications can be thought of within the scope described in the claims, and it can be understood that they certainly also belong to the technical scope of the present invention. In addition, within the scope of not departing from the gist of the invention, the various constituent elements in the above-mentioned embodiments can be arbitrarily combined.
[0188] It should be noted that the present application is based on the Japanese patent application (Japanese Patent Application No. 2022-086808) filed on May 27, 2022, and the contents thereof are incorporated herein by reference.
[0189] Explanation of symbols
[0190] 1. Organic Fiber
[0191] 2 Area 1
[0192] 3 Area 2
[0193] 4Inorganic particles
[0194] 7 Fiber bundles
[0195] 10Heat transfer suppression sheet
[0196] 20a, 20b, 20c battery cells
[0197] 21Imagination Box
[0198] 30 battery case
[0199] 100 battery pack
Claims
1. A heat transfer suppressing sheet comprising inorganic particles and organic fibers, characterized in that: The surface of the optical fiber device includes a first region having stripe-shaped fiber bundles composed of a plurality of the organic fibers and a second region where the fiber bundles are not present.
2. The heat transfer suppressing sheet according to claim 1, wherein: The first region has the stripe-shaped fiber bundles penetrating at least three consecutive imaginary frames of 5 mm square.
3. The heat transfer suppressing sheet according to claim 1, wherein: The first region has the stripe-shaped fiber bundle having a length of 20 mm or more.
4. The heat transfer suppressing sheet according to claim 1, wherein: It has the second region surrounded by the first region.
5. The heat transfer suppressing sheet according to claim 1, wherein: The striped fiber bundles are connected on the surface to form a grid.
6. The heat transfer suppressing sheet according to claim 1, wherein: The inorganic particles are particles composed of at least one inorganic material selected from oxide particles, carbide particles, nitride particles, and inorganic hydrate particles.
7. The heat transfer suppressing sheet according to claim 6, wherein: The inorganic particles include at least one particle selected from the group consisting of dry silica particles and silica aerogels.
8. The heat transfer suppressing sheet according to claim 7, wherein: The inorganic particles further include particles of at least one selected from the group consisting of titanium dioxide, zircon, zirconium oxide, silicon carbide, zinc oxide, and aluminum oxide. 9 . A battery pack comprising a plurality of battery cells and the heat transfer suppressing sheet according to claim 1 , wherein the plurality of battery cells are connected in series or in parallel.
Citation Information
Patent Citations
Heat insulation sheet for battery pack and battery pack
JP2021034278A
Capacitor module, inverter module, and motor unit
JP2022086808A